Autism spectrum disorder (ASD): From public policies to evidence-based practices - Nunes, Débora; Schmidt, Carlo; Nunes Sobrinho, Francisco de Paula (Education Policy Analysis Archives, 2021)
In recent years, Brazil has registered a significant increase in the incidence rate of individuals diagnosed with autism spectrum disorder (ASD). This phenomenon is accompanied by the growing number of inclusive policies and guidebook for educators and health agents, describing interventional practices that guarantee the education/treatment of these individuals in school and non-school settings. The purpose of this literature review, associated with documentary research, was to analyze reference publications, disseminated by the Ministry of Health and Education, which address interventional practices for individuals with ASD, published in the last 20 years. Results from the six documents identified indicated that the conceptions of ASD, the interventions proposed, as well as the professional profiles of those who work with this population were not always aligned with empirically validated protocols. Alternatives for the production, dissemination, and improvement of evidence-based practices (EBP) for students with ASD are discussed.